(untitled) (Third Sector Social Economic Review, 2022)
TAS-2 inventories standard is based on normal cost method, instead of full costing method. The aim of this study is to examine the Resource Consumption Accounting (RCA) method, which has emerged as an important management accounting technique in calculating the idle capacity in recent years, within the framework of TAS-2 inventories standard. For this purpose, both the normal cost management method based on the TAS-2 inventories standard and the RCA method are applied to a production facility. The findings suggest that the RCA method estimates the idle capacity costs accurately, reliably and realistically as proposed by the standard. Therefore, for businesses that have to apply the standards, the RCA method can be easily integrated within their own systems.